2009
DOI: 10.1182/blood-2009-05-174359
|View full text |Cite
|
Sign up to set email alerts
|

How I treat Waldenström macroglobulinemia

Abstract: Waldenströ m macroglobulinemia (WM) is a distinct B-cell disorder resulting from the accumulation, predominantly in the bone marrow, of clonally related IgMsecreting lymphoplasmacytic cells. Genetic factors play an important role, with 20% of patients demonstrating a familial predisposition. Asymptomatic patients should be observed. Patients with a disease-related hemoglobin level less than 10 g/L, platelet count less than 100 ؋ 10 9 /L, bulky adenopathy or organomegaly, symptomatic hyperviscosity, peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
0
7

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(90 citation statements)
references
References 81 publications
(102 reference statements)
0
83
0
7
Order By: Relevance
“…This suggests that the best level of clonal eradication offers the best renal responses, supporting the use of rituximabchemotherapy rather than an alkylating agent or rituximab monotherapy. Of note, a combination of rituximab plus bendamustine, an alkylating agent, has emerged as a promising regimen in patients with previously untreated or refractory non-Hodgkin's lymphoma, WM or CLL [17,18], This steroid-free treatment may be an attractive alternative for some patients with iNHL-associated glomerulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the best level of clonal eradication offers the best renal responses, supporting the use of rituximabchemotherapy rather than an alkylating agent or rituximab monotherapy. Of note, a combination of rituximab plus bendamustine, an alkylating agent, has emerged as a promising regimen in patients with previously untreated or refractory non-Hodgkin's lymphoma, WM or CLL [17,18], This steroid-free treatment may be an attractive alternative for some patients with iNHL-associated glomerulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Current recommendations for frontline therapy of patients with WM include the use of alkylating agents (e.g: chlorambucil or cyclophosphamide), nucleoside analogs, (e.g fludarabine), rituximab alone, and combinations of these agents [12,[14][15][16][17][18]. Long-term exposure to chlorambucil or nucleoside analogs in patients who are eligible for stem cell transplant is not recommended [17].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure to chlorambucil or nucleoside analogs in patients who are eligible for stem cell transplant is not recommended [17]. In addition, recent studies have shown that nucleoside analogs can increase the risk of malignant transformation and myelodysplasia [19].…”
Section: Discussionmentioning
confidence: 99%
“…Waldenstrom macrogloblulinemia (WM) is a distinct lowgrade B-cell lymphoma characterized by the presence of a serum monoclonal IgM protein and lymphoplasmacytic cells in bone marrow [1][2][3][4]. WM is a rare cancer with 1,500 new cases diagnosed per year in the US.…”
Section: Introductionmentioning
confidence: 99%